Performance of Targeted Congenital Cytomegalovirus Screening in Newborns Failing Universal Hearing Screening: A Multicenter Study. Issue 6 (27th January 2022) - Fourgeaud, Jacques; Boithias, Claire; Walter-Nicolet, Elisabeth; Kermorvant, Elsa; Couderc, Sophie; Parat, Sophie; Pol, Christine; Mousset, Carole; Bussières, Laurence; Guilleminot, Tiffany; Ville, Yves; Nkam, Lionelle; et al.
Abstract : Background: Cytomegalovirus (CMV) is the most frequent cause of congenital infection and ≈20% of all infected neonates present or will develop sensorineural hearing loss. Targeted congenital CMV (cCMV) screening in newborns who failed universal newborn hearing screening has been proposed as a strategy to identify neonates with both hearing loss and cCMV infection who could benefit from antiviral treatment implemented within the first month of life. Objectives: To evaluate the feasibility and performance of cCMV targeted screening in a French setting. Methods: Neonates were recruited in 5 maternity centers in greater Paris. A saliva sample for CMV polymerase chain reaction (PCR) testing was collected in neonates who failed newborn hearing screening. Outcomes including CMV PCR result and confirmation of hearing loss by an otorhinolaryngologist specialist were documented. Results: Two-hundred thirty-six newborns were included and a saliva sample was collected in 98% (231/236) of them. The result of CMV PCR was available at a median of 9 days (7–10 days) of life and in 96% of cases within the first month of life. Two neonates were infected with CMV. The result of the otorhinolaryngologist assessment was available in 75% (178/236) of cases at a median of 16 days (9–26 days). Hearing loss was confirmed in 2.8% (5/178). The 2 infected neonates had hearing loss confirmed at 5 and 8 days of life and were treated with valganciclovir at days 9 and 16, respectively. Conclusions: The result of this study confirms that targeted cCMV screening is feasible in these French settings.